The privatisation activities of the Treuhandanstalt and the transformation of the East German corporate landscape data: Data documentation of the IWH-Treuhand-privatisation micro database - Alexander Giebler; Michael Wyrwich (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
Even nearly 30 years after the fall of the Berlin Wall, the privatisation and transformation of East Germany's business landscape is controversially discussed in the media and politics. The privatisation process led to enormous structural changes, which were associated with massive job losses. In particular, the stagnating regional development of East Germany is often blamed on the "long shadow" of the privatisation activities of the Treuhandanstalt (THA). From a scientific perspective, however, there are hardly any contributions dealing with the effects of privatisation activities. The IWH-Treuhand Privatisation Micro Database introduced in this technical report is novel as such that it provides comprehensive information on employment and turnover figures for formerly state-owned enterprises for the early 1990s.
Keywords: 330